Fabrication Chitosan-valine Interpenetrating Polymer Network for Estimation Human Lipid Profile and Total Proteins - Saleh, Ahmed; Adham, Reem; Ghassan, Israa (International Journal of Psychosocial Rehabilitation, 2020)
Present research aimed to determine the efficiency of chitosan-valine bead modification by ethylene glycol diglycidylether (EGDE) as a cross-linker polymer to adsorb lipid profile and total proteins (total cholesterol (TC), triglyceride (TG), low-density lipoprotein (LDL-C), and total protein (TP)) from human serum in patients suffering from hyperlipidemia in different contact times and temperatures. A UV-Vis spectrophotometer was used to determine the concentration of the adsorption before and after adsorption. The modified beads utilized in this research were portrayed by scanning electron microscopy (SEM) to depict the surface of the beads and by infrared (IR) spectroscopy to affirm the cross-linking reaction. The results showed that the adsorption process attains equilibrium within 3 hours and the extent of adsorbate increased with increasing contact time, temperatures, and concentration. The adsorption isotherms are described by means of the Langmuir and Freundlich isotherms. In the in vitro study, it was found that there were significant decreases (p ≤ 0.05) in the levels of serum “TC, TG, LDL-C, and TP,” while the level of HDL showed a non-significant decrease (p ≥ 0.05) after the adsorption process. It was found that the Langmuir and Freundlich equations both fit. Theadsorption kinetics of the adsorbate was best described by the pseudo first-order reaction model. Free energy of adsorption (∆G ), enthalpy (∆H ), and entropy (∆S ) changes were calculated to predict the nature of adsorption.